2013
DOI: 10.3746/jkfn.2013.42.12.1899
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering Effects of Unripe Black Raspberry Water Extract

Abstract: We investigated the effects of unripe black raspberry water extract (UBR-W) and oxidation-LDL treatment on cholesterol levels. Experiments using an established human hepatocellular carcinoma cell line (HepG2) showed a time-dependent increase in expression of LDL receptor after UBR-W treatment. Expression of LDL receptor-related genes, such as SREBP1 and 2, increased upon UBR-W treatment. However, expression of HDL-related genes was unaffected by UBR-W. HMG-CoA reductase activity was reduced by UBR-W treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Concentrates were lyophilized in a freeze dryer. Phenolic and flavonoid compound profiles of RO extract (unripe, extract with 50% ethanol) were analyzed as previously described (Choi et al ., ): ellagic acid 6,352 µg/g; gallic acid 484 µg/g; rutin 160 µg/g; quercetin 114 µg/g; ferulic acid 100 µg/g; caffeic acid 82 µg/g; luteolin 42 µg/g; myricetin 22 µg/g; and kaempferol 12 µg/g. Definite anthocyanins levels of RO extract investigated in this study were not available, although molecular profiles were presented in several previous studies (Lee et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Concentrates were lyophilized in a freeze dryer. Phenolic and flavonoid compound profiles of RO extract (unripe, extract with 50% ethanol) were analyzed as previously described (Choi et al ., ): ellagic acid 6,352 µg/g; gallic acid 484 µg/g; rutin 160 µg/g; quercetin 114 µg/g; ferulic acid 100 µg/g; caffeic acid 82 µg/g; luteolin 42 µg/g; myricetin 22 µg/g; and kaempferol 12 µg/g. Definite anthocyanins levels of RO extract investigated in this study were not available, although molecular profiles were presented in several previous studies (Lee et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…uRC exerts a cholesterol-lowering effect due to its functionally active compounds. According to Choi et al [ 20 ], the components of uRC were analyzed as physiologically active substances. Ellagic acid was reported to be the most abundant ingredient, and the ellagic acid content of unripe fruit was approximately seven-fold higher than ripe fruit [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rubus croreanus Miquel (black raspberry, RC) is part of the Rosaceae family and grows in the Republic of Korea [ 18 ]. The extract of RC contains abundant levels of various natural components, such as ellagic acids, flavonoids, tannins, phenolic acids, organic acids, tyrosol, and resveratrol [ 19 , 20 ]. These pharmaceutically active components exert antihyperlipidemic, anti-inflammatory and antiatherosclerotic effects [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These effects are due to various polyphenolic ingredients contained in raspberry. Previous studies (Choi et al, 2013) reported differences in the content of bioactive substances such as caffeic acid, ellagic acid, ferulic acid, gallic acid, and quercetin in raspberry according to maturity. As a result, the content of ellagic acid was the highest among the various components, and its content was higher in uRo than Ro.…”
Section: Introductionmentioning
confidence: 95%